Elementary School Students' Perceptions of STEM-Based Mobile Learning Applications - Reza Rachmadtullah; Evita Purnaningrum; Suharni Suharni (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractResearch conducted by the "We Are Social" institution shows that Indonesian people are a significant resource in utilizing the internet. The ability of Indonesian elementary school students in using digital technology is quite good; however, its use is primarily for entertainment. Observing this phenomenon, researchers have taken the initiative to harness digital technology to enhance the learning experience, moving away from conventional methods. This study aims to investigate how elementary school students perceive STEM-Based Mobile Learning Application Technology. The research method used for this study is qualitative, emphasizing discourse analysis and conversational analysis. Participants in this study included ten fifth-grade elementary school students in the city of Cirebon. The results of the study have been quite positive, as this application makes it convenient for students to study anywhere and at any time, as long as their smartphones are connected to the internet. Nonetheless, the use of STEM-Based Mobile Learning Application Technology has received feedback regarding its limitations and weaknesses, such as the small screen, which makes it challenging for users to read text.Keywords: mobile learning application, STEM, elementary school students.AbstrakRiset yang dilakukan oleh lembagaÂ We Are SocialÂ menunjukkan bahwa masyarakat Indonesia merupakan sumber daya yang sangat besar dalam mendayagunakan internet. Kemampuan siswa Sekolah Dasar Indonesia sudah cukup baik dalam menggunakan teknologi digital. Namun pemanfaatannya masih bersifat hiburan. Melihat fenomena tersebut, peneliti berinisiatif untuk memanfaatkan teknologi digital untuk memfasilitasi pembelajaran sehingga tidak lagi bersifat konvensional. Penelitian ini bertujuan untuk mengetahui bagaimana persepsi Siswa Sekolah Dasar terhadap Teknologi Aplikasi Mobile Learning Berbasis STEM. Metode yang digunakan untuk jenis penelitian ini adalah metode penelitian kualitatif. menekankan pada fokus analisis wacana dan analisis percakapan Partisipan dalam penelitian ini yaitu melibatkan sepuluh siswa sekolah dasar kelas lima di kota Cirebon. Hasil penelitian ini yaitu Mendapatkan respon yang postif karena apliaksi ini memberikan kemudahan siswa untuk belajar dimanapun dan kapanpun asalkan smartphone mereka terhubung dengan internet. Namun penggunan Teknologi Aplikasi Mobile Learning Berbasis STEM juga mendapatkan respon terkiat kelemahan atau kekurangannya yaitu memiliki keterbatasan seperti perangkat lainnya diantaranya yaitu layarnya kecil sehingga pengguna kesulitan untuk membaca teks.Kata kunci: aplikasi mobile learning, STEM, siswa sekolah dasar.